The Dynastic Benefits of Early Childhood Education: Participant Benefits and Family Spillovers - Frederik H. Bennhoff; Jorge Luis García; Duncan Ermini Leaf (Institute of Labor Economics (IZA), 2023)
We demonstrate the social efficiency of investing in high-quality early childhood education using newly collected data from the HighScope Perry Preschool Project. The data analyzed are the longest follow-up of any randomized early childhood education program. Annual observations of participant outcomes up to midlife allow us to provide a cost-benefit analysis without relying on forecasts. Adult outcomes on the participants' children and siblings allow us to quantify spillover benefits. The program generates a benefit-cost ratio of 6.0 (p-value = 0.03). Spillover benefits increase this ratio to 7.5 (p-value = 0.00).
Keywords: J13; I28; C93; H43; 330; cost-benefit analysis; early childhood education; intergenerational mobility; intergenerational program evaluation; life-cycle benefits; spillover effects